2011
DOI: 10.4047/jap.2011.3.3.145
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immobilization of heparin and bone morphogenic protein-2 to bovine bone substitute on osteoblast-like cell's function

Abstract: PURPOSEThis study was performed to investigate the ability of recombinant human-bone morphogenic protein-2 immobilized on a heparin-grafted bone substrate to enhance the osteoblastic functions.MATERIALS AND METHODSThe Bio-Oss®, not coated with any material, was used as a control group. In rhBMP-2-Bio-Oss® group, rhBMP-2 was coated with Bio-Oss® using only deep and dry methods (50 ng/mL, 24 h). In heparinized rhBMP-2-Bio-Oss® group, dopamine was anchored to the surface of Bio-Oss®, and coated with heparin. rhBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…To facilitate the sustained release of rhBMP-2, Huh et al [39] attempted to chemically immobilize rhBMP-2 to DOPA-heparin on xenogenous bone. However, the chemical approach is challenging clinically and potential chemical toxicity restricts its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the sustained release of rhBMP-2, Huh et al [39] attempted to chemically immobilize rhBMP-2 to DOPA-heparin on xenogenous bone. However, the chemical approach is challenging clinically and potential chemical toxicity restricts its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in agreement with previous studies conducted by Kim et al [ 30 ] and Park et al [ 38 ]. However, in other previous studies, there was no significant increase in cell proliferation observed in substrates with BMP-2 as compared to the substrates without BMP-2 [ 27 29 , 39 ]. Thus, the effect of BMP-2 on cell proliferation is still not clear.…”
Section: Discussionmentioning
confidence: 64%
“…To demonstrate the osteogenic differentiation of MG-63 cells on PCL fibers and surface-modified PCL fibers, we assessed the ALP activity, calcium deposition, and the mRNA gene expressions of OCN and OPN. ALP activity is well known to be able to evaluate the early differentiation of osteoblast-like cells [ 30 , 39 ]. The ALP activity of MG-63 cells cultured on PCL fibers and surface-modified PCL fibers was increased throughout the 10 days of culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that heparin is composed of many sulfate and carboxyl groups and has good binding affinities for BMP-2. Huh et al [41] and Kim et al [42] showed that BMP-2 from Ti and bovine bone (Bio-Oss) modified with heparin were released in a sustained fashion compared to BMP-2 from Ti and bovine bone (Bio-Oss). Consistent with the previous studies, this study showed the sustained release of BMP-2 from BMP-2/Hep-PMS.…”
Section: Discussionmentioning
confidence: 97%